Facile synthesis of two-photon absorbing polymers through radical copolymerization (eXPRESS Polymer Letters, 2007)
A two-photon absorbing polymer has been prepared through radical copolymerization of methyl acrylate and a synthesized monomer containing a two-photon absorbing chromophore (E,E,E)-1,3,5-tristyrylbenzene (1), under conventional radical polymerization conditions. The synthesized polymer was characterized by nuclear magnetic resonance (NMR), infra-red spectroscopy (IR) and gel permeation chromatography (GPC). The linear and nonlinear optical properties were studied by measurement of UV-Vis absorption, fluorescent emission and two-photon cross-section. This synthetic strategy provided a facile approach for synthesis of photonic materials with adjustable chromophore concentration and high molecular weights.